Avaliação da qualidade da água para fins de irrigação na área aluvional do município de Limoeiro do Norte - Porto, Zilberto Barbosa (1995)
The work was done, from october 1993 to june 1994, at the Jaguaribe river valley, Limoeiro county, state of Ceará, Brazil, with the objective of determining possible seasonal variations in water quality for irrigation and leaching requirements. Water samples were collected monthly from 20 different places, in river beds, large diameter shallow wells ("Amazon wells") and shallow tubular wells, and classified according to the U.S. Salinity Laboratory and the University of California Consultants Committee norms. Minimun leaching requirements were also determined for the main crops in the study area. The results shown that the parameters from the same sampling place had only small variations and did not interfere with the water classification, during the observation period. But, when the analytical results from the three different sources (river beds, large shalow wells and tubular shalow wells) were compared, this induced significant variations for water classification. Minimum leaching requirements ranged from 1.53% to 11.63%, according to the salt tolerance of the different crops in the area, for a 90% yield probability.